Footsteps in the dark - Meniru E. Theresa (Macmillian Nigeria, 1982)
This is the thrilling tale of Uche Okafor alias Uche Barrow. Two men come to him one evening to offer what seems to be a fine opportunity for a poor boy to make his way in the world. But from beginning to end, nothing happens as anyone expects. The footsteps of each new character brings more complications and dangers for Uche until the very end of the exciting story.
Keywords: Juvenile Fiction / Adventure / Complications